Short-term efficacy and safety of rituximab therapy in refractory systemic lupus erythematosus: results from the British Isles Lupus Assessment Group Biologics Register. (5th December 2017) - McCarthy, Eoghan M; Sutton, Emily; Nesbit, Stephanie; White, James; Parker, Ben; Jayne, David; Griffiths, Bridget; Isenberg, David A; Rahman, Anisur; Gordon, Caroline; D'Cruz, David P; Rhodes, Benjamin; et al.
Abstract: Objectives: To describe the baseline characteristics of SLE patients requiring biologic therapy in the UK and to explore short term efficacy and infection rates associated with rituximab (RTX) use. Methods: Patients commencing biologic therapy for refractory SLE and who consented to join BILAG-BR were analysed. Baseline characteristics, disease activity (BILAG 2004/SLEDAI-2K) and rates of infection over follow-up were analysed. Response was defined as loss of all A and B BILAG scores to ⩽ 1 B score with no new A/B scores in other organ systems at 6 months. Results: Two hundred and seventy SLE patients commenced biologic therapy from September 2010 to September 2015, most commonly RTX ( n = 261). Two hundred and fifty (93%) patients were taking glucocorticoids at baseline at a median [interquartile range (IQR)] oral dose of 10 mg (5–20 mg) daily. Response rates at 6 months were available for 68% of patients. The median (IQR) BILAG score was 15 (10–23) at baseline and 3 (2–12) at 6 months ( P < 0.0001). The median (IQR) SLEDAI-2K reduced from 8 (5–12) to 4 (0–7) ( P < 0.001). Response was achieved in 49% of patients. There was also a reduction in glucocorticoid use to a median (IQR) dose of 7.5 mg (5–12 mg) at 6 months ( P < 0.001). Serious infections occurred in 26 (10%) patients, being more frequent in the first 3 months post-RTX therapy. A higher proportion of early infections were non-respiratory (odds ratio = 1.98, 95% CI: 0.99, 3.9; P = 0.049). Conclusion: RTX is safe and is associated with improvement in disease activity in refractory SLE patients with concomitant reductions in glucocorticoid use. Early vigilance for infection post-infusion is important to further improve treatment risks and benefits.